Congenital candidiasis in a full-term infant: A case report. Issue 4 (April 2023) - Zhao, He-Hua; Zhe-Zhou; Lu, Lu; Zhao, Yong-Ze; Yang, Li-Jun; Ding, Ying-Xue
Congenital systemic candidiasis is a rare disease observed in both full-term and preterm infants. It can occur with or without congenital cutaneous candidiasis (CCC) and to date, only a few cases have been reported in the literature. We report here, a case of a full-term newborn who presented with diffuse skin eruptions at birth. Blood, urine, and skin scraping cultures were positive and the aetiological agent was Candida albicans . After six weeks of anti-fungal treatment with fluconazole, the newborn was cured. Early diagnosis is crucial in preventing complications caused by candidiasis in newborns.